Menopausal characteristics and hormone replacement therapy in relation to long-term risk of cholecystectomy in women - Ding, Guan-Jun; Jiang, Wei; Lyu, Jie-Qiong; Ma, Jie; Chen, Guo-Chong; Li, Fu-Rong; Yang, Si-Jia; Miao, Meng-Yuan; Hua, Yong-Fei (Frontiers in Medicine, 2024)
Background: Women are known to be at higher risk for gallbladder disease than men, suggesting a role of female hormones in the pathogenesis of gallbladder disease. This study aimed to assess menopausal characteristics, hormone replacement therapy (HRT) and their joint effect on longterm risk of cholecystectomy in women.Methods: A total of 184,677 women were included from the UK Biobank. Multivariable Cox regression models were used to estimate the associations of menopausal characteristics and HRT with risk of cholecystectomy. The joint influence of HRT use and the status and type of menopause on incident cholecystectomy were further evaluated.Results: During a median of 12.7 years of follow-up, 4991 incident cases of cholecystectomy were identified. Natural menopause, regardless of menopausal age, was not associated with risk of cholecystectomy, while surgical menopause at a young age was associated with a higher risk of cholecystectomy. Ever use of HRT was associated with a higher risk of cholecystectomy. In particular, women who were surgically-menopausal and started HRT before menopause had the highest risk for cholecystectomy (hazard ratio = 2.28; 95% confidence interval: 1.70-3.04), when compared with women who were naturally-menopausal and never used HRT.Early surgical menopause and ever use of HRT was independently associated with the risk of cholecystectomy.